Systematic review of Atractus schach (Serpentes: Dipsadidae) species complex from the Guiana Shield with description of three new species. Issue 3 (3rd April 2019) - Melo-Sampaio, Paulo Roberto; Passos, Paulo; Fouquet, Antoine; Prudente, Ana Lucia Da Costa; Torres-Carvajal, Omar
Abstract : The Guiana Shield harbours one of the best preserved and largest extents of tropical forest on Earth and an immense biodiversity. The herpetofauna of this region remains poorly known. The species-rich snake genus Atractus contains ∼140 species, many with complicated taxonomic histories, including A. schach . Examination of specimens in museums and newly collected material from French Guiana has allowed the illustration of hemipenial morphology for the first time and an expanded diagnosis. Concatenated molecular phylogenetic (mitochondrial and nuclear genes) and phenotypic (morphometrics, external and hemipenial morphology) analyses confirm non-monophyly of the A. flammigerus group and indicate that A. schach is a species complex with three new species described here. The geographic distribution of A. schach sensu stricto is restricted to Guiana, Surinam, and French Guiana north of Tumucumaque massif. Populations tentatively assigned to A. schach from the east from French Guiana in the Roura lowlands to Almeirim, and from central Amazonia between the Negro and Trombetas rivers in Brazil are also recognized as new species. Our results suggest that populations from south of the Amazon River are not conspecific with those from the Guiana Shield. http://www.zoobank.org/urn:lsid:zoobank.org:pub:A7AE40BC-4716-4302-B3BE-1F43600B0A72